(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To assess patient satisfaction with healthcare at the Tien Giang provincial General Hospital. Method: Cross-sectional descriptive study. Results: The overall patient satisfaction rate with the mental care provided by nurses at Tien Giang provincial General Hospital was 98.4%; satisfaction with the execution of nursing care activities was 98.7% (the highest); satisfaction with the relationship between patients and nurses was 96.6%. The overall patient satisfaction rate for all nursing care activities was 98.4%. Conclusion: The patient satisfaction rate is very high (all from 96.6% and above), with the highest being 98.7% of patients satisfied with the nursing care activities. There was no significant difference in patient satisfaction rates between inpatient and outpatient groups, with p-values > 0.05. The overall patient satisfaction rate for all nursing care activities was 98.4%.